2009
DOI: 10.1159/000257528
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Slices from Adult Mammalian Hearts as a Model for Pharmacological Drug Testing

Abstract: Aim: Isolated papillary muscles and enzymatically dissociated myocytes of guinea-pig hearts are routinely used for experimental cardiac research. The aim of our study is to investigate adult mammalian ventricular slices as an alternative preparation. Method: Vibratome cut ventricular slices (350 μm thick) were examined histologically and with 2-photon microscopy for fibre orientation. Intracellular action potentials were recorded with conventional glass microelectrodes, extracellular potentials were measured w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 38 publications
(35 reference statements)
4
64
0
Order By: Relevance
“…Live heart tissue slices were prepared from the left ventricle of 4-6 months mdx mice [34]. In brief, hearts were rapidly excised, ventricular tissue blocks were dissected and mounted onto the specimen holder of a high precision vibratome (7000 smz, Campden Instruments, UK), in ice-cold Tyrode solution.…”
Section: Methodsmentioning
confidence: 99%
“…Live heart tissue slices were prepared from the left ventricle of 4-6 months mdx mice [34]. In brief, hearts were rapidly excised, ventricular tissue blocks were dissected and mounted onto the specimen holder of a high precision vibratome (7000 smz, Campden Instruments, UK), in ice-cold Tyrode solution.…”
Section: Methodsmentioning
confidence: 99%
“…The activated human factor X (FXa) was used in the concentration of 50 nM (Dunn, Germany). The viability of human atrial tissue slices cultured or stimulated in vivo was confirmed using established vital staining technique (CellTracker Green CMFDA, Invitrogen, Karlsruhe, Germany) (Bussek et al, 2009). The living slices were incubated for 1-2 h with the final concentration of 5 mM dye in serum-free medium and imaged as stitched mosaic with a fluorescent microscope (Zeiss Axiovert 200 m) using an excitation wavelength filter of 480/40 nm, a diachroic filter 505 nm long pass and emission wavelength between filter of 535/50 nm.…”
Section: Culturing Tissue Slices and "In Vitro" Pacingmentioning
confidence: 99%
“…1), pulmonary vein sleeves, ventricular slices as well as trabeculae and papillary muscles are widely used in experiments to study the physiology of cardiac function in health and disease [5, 21, 22, 40]. Unlike in isolated myocytes, gap junctions and extracellular matrix are preserved, allowing to characterize electrophysiological function under conditions similar to those in intact hearts (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to larger preparations, where perfusion is essential to ensure adequate oxygen supply as well as wash out of waste products throughout the preparation [47], due to its simplicity, superfusion with oxygenated solutions is typically employed for thin-walled tissue samples [5, 17, 2123, 40]. Although superfusion is adequate to maintain preparations viable for prolonged experimental procedures, this is not the case with larger samples where the thickness of the muscle wall exceeds the diffusion length [2].…”
Section: Introductionmentioning
confidence: 99%